Alive agile leadership in the COVID-19 era / Yazrina Yahya ... [et al.] - Mohd Nordin, Nordiana; Mat Isa, Azman; Sarmin, Nor Haniza; Anwar, Norizan; Yahya, Yazrina (UiTM Press, 2022)
The past decade has been challenging due to COVID-19 pandemic, the change in world climate which results in typhoons, earthquakes, and volcano eruptions, that pose several unforeseen challenges not only to the global population but also to the higher learning institutions (HLIs) directly or indirectly. Like any other organisation, HLIs must adapt to the current challenging situation to ensure they can continue to manage their various stakeholders effectively - particularly academics, administrative staff, researchers, and most importantly, the students, to prepare and contribute to the organisation during difficult times. In addition, organisations must adapt to the challenges and be resilient. Hence, leaders of higher education institutions need to be agile and align them with agile principles. It is to ensure that the HLI transforms into an agile organisation and adapts to weather major unforeseen disruption and achieve its target results; thus, it is the basis of Agile Leadership in the COVID-19 era. The new kind of agile organisation requires a fundamentally different kind of leadership. Leaders need new sets of capabilities for agile transformations. Agile leadership requires the leader to establish a common purpose and clear communications to get the people in the institution to feel personally invested in the company. It requires the leaders to set up a structure that allows rapid decision-making, which ensures long-term sustainability, creating networks of local teams with clear and accountable roles via empowerment and flat structures. In addition, an agile leader will also provide people with the technology they need, which is the core of every aspect of an organisation. It is fundamental to ALiVE.